EFEK VIDEO PERAWATAN BAYI BERAT LAHIR RENDAH SAAT DISCHARGE PLANNING TERHADAP KETERAMPILAN ORANG TUA - Veniawati, Okti; Rahmawati, Eni; Susmarini, Dian (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Background: Low Birth Weigh Babies (LBWB) were at high risk of experiencing hyphothermia and lack of nurtition due to the weakness in suction reflex. That issue could be a cause for babies to be long hospitalized. The risk can be tackled with practicing the right breastfeeding technique and Kangaroo Mother Care (KMC) technique. Method: This type of research was quantitative with quasy experimental pretest and posttest with control group design. The sampling technique used quota sampling. Each group had 18 repondents made the total of respondents to be 36 people. The instruments in this research were observation sheets of breastfeeding and KMC. Result: It was obtained the score of breastfeeding with P value = 0.005 and KMC with P value = 0.016 in which both had P value = <0.05. There was significant difference of the video on the mother skill of breastfeeding and KMC. Conclusion: Home care video for Low Birth Weight Baby was effective in improving the parent?s skill on breastfeeding and KMC technique.